PYTHON YORDAMIDA BULUTL TEXNOLOGIYALARNI O‘RGATUVCHI TELEGRAM BOT ISHLAB CHIQISH - S.P. Kutliyev; Sh.F. Reyimbayev; Z.M.Rahimberdiyev (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, practical work on the creation and use of a telegram bot that teaches cloud technologies using the Python programming language has been developed.